Lean Fish Consumption Is Associated with Beneficial Changes in the Metabolic Syndrome Components: A 13-Year Follow-Up Study from the Norwegian Tromsø Study - Tørris, Christine; Molin, Marianne; Småstuen, Milada C (Nutrients, 2017)
Background: Fish consumption may have beneficial effects on metabolic syndrome (MetS); however, limited information of such associations exists. This study investigated possible associations between fish consumption and changes in MetS components during a 13-year follow-up period. Methods: The sample included participants (26–69 years) from the Tromsø Study 4 (1994–1995, n = 23,907) and Tromsø Study 6 (2007–2008, n = 12,981). Data were collected using questionnaires including food frequency questions, non-fasting blood samples, and physical examinations. MetS was defined using the Joint Interim Societies (JIS) definition, in which one point was given for each MetS criteria fulfilled (metabolic score). Longitudinal analyses were performed using Linear mixed models. Results: For both genders, lean fish consumption once a week or more was significantly associated with decreased future metabolic score, decreased triglycerides, and increased high-density lipoprotein (HDL)-cholesterol, whereas decreased waist circumference and blood pressure was identified only for men (age adjusted models). Fatty fish consumption was significantly associated with increased waist circumference for both genders and increased HDL-cholesterol levels in men. Conclusion: The results suggest that fatty and lean fish consumption may influence MetS differently and that lean fish consumption in particular seems to be associated with beneficial changes in the MetS components.